Implementasi Manajemen Supervisi Klinis Kolaboratif Berbasis Pengelolaan Kinerja Guru dalam Meningkatkan Kompetensi Pedagogik Guru di SD Negeri 1 Sindang - Wahyu Septiani; Muh. Hanif; Ali Muhdi; Sa’diyah Handayani; Sri Winarsih (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Academic supervision in elementary schools is still often focused on fulfilling administrative requirements related to teaching and learning, and thus does not yet fully support the continuous improvement of teachers’ pedagogical competencies. This study aims to describe the implementation of collaborative clinical supervision management based on Teacher Performance Management in enhancing teachers’ pedagogical competencies at SD Negeri 1 Sindang. The study employed a qualitative approach using a case study design. The research subjects consisted of the principal and six teachers. Data were collected through interviews, observations, and document analysis, which included Teacher Performance Management documents, clinical supervision results, teacher reflections, and follow-up plans. Data validity was ensured through triangulation of sources and techniques, while data analysis utilized the interactive model by Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and the drawing and verification of conclusions. The results of the study indicate that the implementation of clinical supervision is carried out through the stages of Teacher Performance Management analysis, an initial meeting (pre-conference), classroom observation, reflection (post-conference), and follow-up. Using Teacher Performance Management data as the basis for supervision enables school principals to objectively identify teachers’ professional development needs, design more targeted professional development programs, and provide guidance tailored to each teacher’s specific needs.  This implementation has led to an increase in teachers’ ability to design learner-centered instruction, implement differentiated instruction, utilize formative assessment, engage in instructional reflection, and develop ongoing follow-up strategies. This study produced a model for implementing collaborative clinical supervision management based on Teacher Performance Management, which integrates teacher performance data into all stages of supervision as a strategy for improving teachers’ pedagogical competencies and the quality of learning in schools.